Black queer flesh : rejecting subjectivity in the African American novel - Henry, Alvin J. (University of Minnesota Press, 2020)
"A groundbreaking examination of how twentieth-century African American writers use queer characters to challenge and ultimately reject subjectivity"-- Provided by publisher.
Keywords: African American gay people in literature.; American fiction -- African American authors.; American fiction -- 20th century.; Homosexuality in literature.; African Americans in literature.; Self in literature.; Personnes homosexuelles noires américaines dans la littérature.; Roman américain -- Auteurs noirs américains.; Roman américain -- 20e siècle.; Homosexualité dans la littérature.; Noirs américains dans la littérature.; Moi (Psychologie) dans la littérature.; LITERARY CRITICISM / American / African American